Interaction-Specific Changes in the Transcriptome of Polynucleobacter asymbioticus Caused by Varying Protistan Communities - Beisser, Daniela; Bock, Christina; Hahn, Martin W.; Vos, Matthijs; Sures, Bernd; Rahmann, Sven; Boenigk, Jens (Frontiers in Microbiology, 2019)
We studied the impact of protist grazing and exudation on the growth and transcriptomic response of the prokaryotic prey species Polynucleobacter asymbioticus. Different single- and multi-species communities of chrysophytes were used to determine a species-specific response to the predators and the effect of chrysophyte diversity. We sequenced the mRNA of Pn. asymbioticus in communities with three single chrysophyte species (Chlorochromonas danica, Poterioochromonas malhamensis and Poteriospumella lacustris) and all combinations. The molecular responses of Pn. asymbioticus significantly changed in the presence of predators with different trophic modes and combinations of species. In the single-species samples we observed significant differences related to the relative importance of grazing and exudation in the protist-bacteria interaction, i.e. to the presence of either the heterotrophic Ps. lacustris or the mixotrophic C. danica. When grazing dominates the interaction, as in the presence of Ps. lacustris, genes acting in stress response are up-regulated. Further genes associated with transcription and translation are down-regulated indicating a reduced growth of Pn. asymbioticus. In contrast, when the potential use of algal exudates dominates the interaction, genes affiliated with iron transport are up-regulated. Rapid phototrophic growth of chrysophytes, with a high demand on soluble iron, could thus lead to iron-limitation and cause changes in the iron metabolism of Pn. asymbioticus. Additionally, we observe a benefit for Pn. asymbioticus from a more diverse protistan community, which could be due to shifts in the relative importance of phototrophy in the mixotrophic chrysophytes when competing for food with other species. Our study highlights the importance of biotic interactions and the specificity of such interactions, in particular the differential effect of grazing and algal exudation in the interaction of bacteria with mixotrophic protists.